The Integration of Artificial Intelligence in Histopathological Diagnostics: Review of Methodologies, Efficacy, and Future Directions in Clinical Practice - Hazzazi, Ahmad Mohammad Tyhan; Halawi, Hussain Ali; Jabbari, Fuad Ali Abdu; Alabdali, Ali Ibrahim; Safhi, Basem Mohammed Mousa; Kinani, Essa Mohamed Ahmed; Daghriri, Ahmed Ali; Hamzi, Hussain Dyab Ahmed; Gharwi, Abdu Hadi Hamoud; Sharahili, Aishah Ali Ali; Khawaji, Abdulmajeed Mohsen Ali (Journal of Ecohumanism, 2024)
The integration of artificial intelligence (AI) in histopathological diagnostics represents a transformative advancement in healthcare, facilitating enhanced accuracy in disease detection and treatment planning. AI technologies, including machine learning and deep learning, have the potential to analyze complex data sets, improving diagnostic capabilities across various medical fields.This review systematically evaluates current literature on the application of AI in histopathological diagnostics, focusing on its methodologies, efficacy, and integration within clinical workflows. A comprehensive search was conducted across multiple databases, including MEDLINE, EMBASE, and CINAHL, to identify relevant studies published up to 2023.The findings indicate that AI technologies, particularly deep learning algorithms, demonstrate superior performance in identifying histopathological features compared to traditional methods. AI's ability to analyze large volumes of data enables the detection of subtle patterns that may elude human observers. Studies highlighted the successful application of AI in diagnosing various cancers, including breast and lung cancers, showcasing improved diagnostic accuracy and efficiency.The integration of AI in histopathology holds significant promise for enhancing diagnostic precision and optimizing patient care. However, challenges remain in the form of regulatory approval, clinical implementation, and the need for robust training datasets. Continued research and collaboration among pathologists, data scientists, and healthcare professionals are essential to fully realize the potential of AI in histopathological diagnostics.